WITHDRAWN: Balancing the genetic risk of APOL1 kidney disease variants - (:unkn) unknown (My University, 2019)
African-Americans exhibit an excess risk for chronic and end-stage kidney disease compared to the non-African populations. Two APOL1 genetic variants were shown to account for the majority of this racialdisparity in glomerulopathies and other non-diabetic kidney disease. The high-risk genotype has onlybeen reported in populations with recent African ancestry (14 % in African-Americans and up to morethan 30 % in West Africa). In less than 10 years, the community has accumulated extensive knowledge onAPOL1 and its genetic variants, from their positive selection for resistance against African trypanosomesto potential molecular mechanisms of podocyte injury. Finally, APOL1 associations with kidneytransplantation outcomes and with postdonation end-stage kidney disease in living donors have pavedthe way for a personalized medicine implementation of APOL1 genotyping.
Keywords: African Research